Comparative Analysis of the Implementation of United Nations Rights-Based Approach to Early Childhood Education Programme in Two Anglophone Countries - THOMAS, Ifueko Omowunmi; MANUEL, Mojisola Nkechi (Ilorin Journal of Education, 2024)
The United Nations Rights-based approach to education programme, conceived in the year 2007, targets the holistic development of every child in every nation. However, since the adoption of the Education for All (EFA) protocol by signatory nations, the notion of rights based approach within the context of early childhood education appeared to remain a mere rhetoric. Using the UNESCO’s EFA framework, this study carried out a comparative analysis of the implementation of the rights-based approach to early childhood education in two signatory West Africa nations: Nigeria and Ghana. Three research questions and one hypothesis guided the study. The study involved four hundred and twenty (420) respondents comprising 200 teachers each from Lagos and Accra and 10 Education Officers selected from 10 Education Authorities in Lagos and Accra each. Adopting the descriptive survey design, the study collected data by means of questionnaires, interview schedule, and checklist guide. The quantitative data analysis involved percentages and ANOVA while the qualitative data were analysed using thematic approach. Findings of this study revealed that provision of adequate instructional materials remains a major challenge to the implementation of rights based approach to education in the two countries. The study concluded that the present status of implementation of ECE programmes curriculum in the two countries fall short of the EFA specified rights-based approach. Based on the findings, the study recommends, amongst others, that all duty-bearers should strive to address all the identified challenges limiting the implementation of rights-based approach to ECE.